2014
DOI: 10.4172/2252-5211.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Current Review on the Coagulation/Flocculation of Lignin Containing Wastewater

Abstract: Agro based industries including pulp and paper mill, palm oil mill, textile, dairy parlour etc. are characterised by its water intensive nature. The pollution problems related to the agro-based industries wastewater are colour, odour and toxicity. Lignin is the major colorant in the agro based industry wastewater. This review is dedicated to explore the lignin and its removal from wastewater via coagulation/flocculation. Over the years, several studies have been conducted for lignin removal using coagulation/f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…To address these drawbacks, the development of a new alternative material is needed. Desirable properties for alternative hybrid materials include greater separation performance, lower dosage, reduced sludge production, and non-aggregation with sludge to enhance recyclability (Cassey & Shazwan 2014;Lee et al 2012;Roopan 2017). More specifically, a material that can simultaneously act as a coagulant-flocculant is desired to simplify the operation and decrease the size of the treatment facility.…”
Section: Introductionmentioning
confidence: 99%
“…To address these drawbacks, the development of a new alternative material is needed. Desirable properties for alternative hybrid materials include greater separation performance, lower dosage, reduced sludge production, and non-aggregation with sludge to enhance recyclability (Cassey & Shazwan 2014;Lee et al 2012;Roopan 2017). More specifically, a material that can simultaneously act as a coagulant-flocculant is desired to simplify the operation and decrease the size of the treatment facility.…”
Section: Introductionmentioning
confidence: 99%
“…High membrane cost, requirement of resin fouling, resin regeneration [22,23] Coagulation and flocculation Settling and dewatering of sludge High cost, large consumption of chemicals [24,25] Membrane filtration [7,30] The majority of these methods [7,[18][19][20][21][22][23][24][25][26][27][28][29][30] are expensive, ineffective in certain concentrations, or time-consuming, and adsorption is limited by the cost of the adsorption material [1,[6][7][8][9]31,32]. For these reasons, the choice of sorbent is crucial for the development of a simple, efficient, inexpensive, and environmentally friendly water purification method [33,34].…”
Section: Advantages Disadvantages Referencementioning
confidence: 99%
“…Variations in the particle size of solids in black liquor were not measured in this study. However, it has been reported that low molecular weight lignin is agglomerated with a coagulant such as aluminum or metal ions (Yaser et al 2014). According to Richardson (1988), the mean particle size of kraft lignin from pulp mills was in the range of 8.6 to 26.1 μm.…”
Section: Effect Of Alum On Black Liquor Viscositymentioning
confidence: 99%